The price impact of CDS trading - Yalin Gündüz; Julia Nasev; Monika Trapp (Deutsche Bundesbank, 2013)
In this paper we show that informational and real frictions in CDS markets strongly affect CDS premia. We derive this main finding using a proprietary set of individual CDS transactions cleared by the Depository Trust & Clearing Corporation. We first show that CDS traders adjust the CDS premium in response to the observed order flow. Buy orders lead to an increase of the premium and sell orders to a decrease, suggesting that the order flow carries information. Second, we show that traders adjust the premium more for transactions with higher inventory risk. Third, trading with buy-side investors who presumably have less market power increases this effect. Overall, our results imply that CDS premia contain a significant non-default related component which CDS traders charge to protect themselves against informational and real frictions.
Keywords: G12; G14; 330; CDS; frictions; asymmetric information; inventory risk; market power